Urbanization and its Effect on Land Surface Temperatures in Halabja City - Othman Baram, Hasim; Ashraf Mohammed, Osama; Kamal Hamaamin, Hemn; Ali Hamid, Arieann; Luqman Mustafa, Rebaz (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The process of rapid urbanization has caused many eco-environmental issues such as rapid changes in land use and the development of urban heat islands. The research studies the changes that have occurred in land use land cover due to enhanced political and socioeconomic growth. The study has used three satellite images (two Landsat 5-TM and Landsat OLI_TIRS-8) from 1999, 2009 and 2019 to investigate the impact of land use and land cover change on LST. Supervised classification was utilized to calculated land LULC map and to compute the LST maps the Mono-Window logarithm was used. In addition, the study attempts to detect the relationship between LST and vegetation area; for this purpose the study also has used images to create NDVI maps. The result showed that the land use change was an important factor for LST increase. The lowest temperatures are associated with vegetation area, ranging from 30, 31 C, while the higher temperatures are associated with barren land and built-up areas, ranging from 44, 45, 53 C.